Ecofeminist Reading of Grapes of Wrath: Women as Life Giving Force - Thapa , Rena (Journal of the Institute of Engineering, 2023)
This paper makes study of John Steinbeck’s portrayal of two female characters as life giving force in his novel The Grapes of Wrath by adopting the ecofeminist theory and perspective as its modality. The main objective of this article is to explore the two female characters, Ma Jode and Rose of Sharon who endure the adverse external forces as the nature herself- reviving, renewing and resuscitating - to live and save life. The two strong female members of Joad family, Ma Joad and Rose of Sharon maintain their spirit of bounty and compassion high throughout the time of crisis. Ma joad’s role expands with the shift in stereotypical gender role at the household of Joads when Pa Joad who is tied to land loses his ego and spirit, and gradually becomes nostalgic. Ma’s holding the powerful stature in the family in turn exhibits the vital power of hope for survival. She is a symbolic matriarchal power to reinforce human connection who sustains heroic will to survive and to humanize natural instinct during the massive economic threat on the family. Ma and Pa both are trapped on the inflow of change of time and space; however Ma’s philosophy of flow underlies her movement to change. Though Ma Joad and Rose of Sharon are stripped off of their domesticity and maternity respectively they preserve the spirit of compassion to save humanity.